Barriers and challenges for primary and secondary prevention of heart disease in sub-Saharan Africa - Stewart, Simon; Carrington, Melinda J.; Sliwa, Karen (SA Heart Journal, 2017)
The diverse people of sub-Saharan Africa face a number of paradoxical challenges arising from economic development and urbanisation, including an increasing prevalence of noncommunicable forms of heart disease. Prevention programmes designed not only to detect those with established and often disabling forms of heart disease, but prevent disease progression and a premature death, are an obvious priority in this setting. This review article reflects on the barriers and challenges to effective primary and secondary prevention of heart disease in sub-Saharan Africa by (a) examining what residual issues challenge effective prevention in high-income countries? (b) what are the key ingredients to an integrated programme of primary and secondary prevention across the lifespan (from the population to individual)? and (c) considering the first two points, what are the barriers and challenges in sub-Saharan Africa to implementing cost-effective primary and secondary prevention using a systematic approach to “who, what and how”?